Control of microstructure and mechanical properties of sintered aluminum nitride through addition of aluminum nitride whiskers. Issue 3 (3rd July 2021) - Kondo, Naoki; Shimamura, Akihiro; Hotta, Mikinori; Shimizu, Hiroki; Ujihara, Toru; Ohnishi, Yoshihiro
ABSTRACT: Aluminum nitride (AlN) usually exhibits a microstructure consisting of equiaxed grains. However, these grains do not allow for the positive control of the microstructure and mechanical properties of AlN. In this work, we attempted to control the microstructure of AlN through the addition of whiskers and investigated the relationship between the microstructure and mechanical properties. The sintered AlN showed a microstructure consisting of large, rod-like grains, which originated from the whiskers. Furthermore, the microstructure varied with the size and amount of whiskers added, and so did the flexural strength and fracture toughness. The flexural strength and fracture toughness of the whisker-added AlN samples ranged from 197 to 267 MPa and 5.4 to 6.4 MPa m 1/2, respectively. In contrast, those of AlN without whiskers were 336 MPa and 3.1 MPa m 1/2, respectively.